Prognostic prediction of apparent diffusion coefficient obtained by diffusion‐weighted MRI in mass‐forming intrahepatic cholangiocarcinoma. (6th April 2020) - Yamada, Shinichiro; Morine, Yuji; Imura, Satoru; Ikemoto, Tetsuya; Arakawa, Yusuke; Saito, Yu; Yoshikawa, Masato; Miyazaki, Katsuki; Shimada, Mitsuo
Abstract: Background: We evaluated apparent diffusion coefficient (ADC) of diffusion‐weighted image MRI as a prognostic factor for mass‐forming intrahepatic cholangiocarcinoma (IHCC). Methods: We enrolled 26 patients who had undergone hepatic resections for mass‐forming‐type IHCC in this study, and calculated their mean ADC, using diffusion‐weighted image MRI ( b : 0, 20, 800 seconds/mm 2 ; 1.5 T MRI). Patients were divided into the ADC High and the ADC Low groups at the median ADC value (n = 13 for both). We also immunohistochemically evaluated hypoxia‐inducible factor (HIF)‐1α in tumor tissue. Results: Median age in the ADC Low was older ( P  = .03), and showed significant higher rate of scirrhous tumor ( P  = .02). The 5‐year overall survival rate in the ADC Low group was significantly worse than in the ADC High group ( P  = .04). In multivariate analysis, hilar tumor, portal vein invasion and low ADC were independent prognostic factors ( P  < .05). The ADC Low group also had a higher rate of high HIF‐1α expression than the ADC High group ( P  < .05). Representative case of ADC Low group showed rich stroma and high HIF‐1α expression. Conclusions: The ADC values in MRIs can predict IHCC prognosis, and correlated with stromal density and HIF‐1α expression. Abstract : Highlight Yamada et al investigated the relationship between the MRI apparent diffusion coefficient value and prognosis of intrahepatic cholangiocarcinoma in 26 patients who underwent initial hepatic resection for mass‐forming intrahepatic cholangiocarcinoma. A low apparent diffusion coefficient value correlated with abundant desmoplastic stroma, poor blood flow, high HIF‐1α expression and worse prognosis.